ANALISIS PERPUTARAN MODAL KERJA PADA CV. YUREZ JAYA MANDIRI (YJM) DI KECAMATAN MUARA BADAK - Aliyasdin, Aliyasdin; Zainuddin, Muhammad; Abdullah, Rahim (I-Con Media, 2021)
he purpose of this study was to determine the working capital turnover in the CV. Yurez JayaMandiri in Muara Badak District in 2018 - 2019. The analytical tool used is cash turnover, inventoryturnover, accounts receivable turnover and working capital turnover. Data sources are the incomestatements and balance sheets of 2018 and 2019. Average cash CV. Yurez Jaya Mandiri in 2018Rp. 4,451,096,000 and in 2019 Rp. 7,458,547,200. Cash turnover in 2018 amounted to 1.29 timesand 2019. Cash turnover period generated in 2018 for 279 days and in 2019 amounted to 486days. Average receivables from CV. Yurez Jaya Mandiri in 2018 Rp. 145,050,000 and in 2019 Rp.117,900,000. Receivables turnover in 2018 amounted to 39.71 times and 2019 46.82 times.Receivable turnover period for 2018 for 9 days, and 2019 for 8 days. Average inventory of CV.Yurez Jaya Mandiri in 2018 Rp. 186,750,000 and in 2019 Rp. 231,400,000. Inventory turnover in2018 was 30.84 times and 2019 was 23.85 times. Inventory turnover period in 2018 for 12 days, in2019 of 16 days. The average working capital of CV. Yurez Jaya Mandiri in 2018 Rp.5,214,541,200 and in 2019 Rp. 8,081,302,200. working capital turnover speed of 1.10 times. Thisvalue is faster than 2019 0.68 times. In 2018 the working capital turnover is 327 days, this numberis faster than in 2019 which is 529 days.Keywords: cash, accounts receivable, inventory, working capital